Sobre uma cultura do mal-estar com a política - Ribeiro, Gustavo César de Macêdo (2006)
The current dissertation has as its main object of study the malaise with politics phenomenon. To comprehend it, is carried out in this work a inquiry, in different stages of analysis, based in the empirical data raised by the research Os Processos Sociais de Recepção do Horário Gratuito de Propaganda Eleitoral , made by the Grupo de Estudos Mídia e Poder, of the Universidade Federal do Rio Grande do Norte, during the local elections of 2004 in the city of Natal. Based in the focus group technique, such research raised an ample set of information about the decoding process of the electoral television programs, made by six different groups of citizens from the popular classes. Beginning from the presuppose which such process is influenced by the representations about politics made by those subjects, we use that set of empirical information to inquiry not only the decoding, but that same representations which this process is based. In this way, we analyse, in one side, the globally contrary decoding which subjects made from a conforming code of opposition and, in the other, the structure of feeling which it s based, called structure of feeling of the malaise with politics. Such structure is compound by generating themes which expresses the contraposition about the institutionalized politics and, in the same time, a resignation about politics which fortifies the dominant groups hegemony. We support the thesis which this set of representations about politics is caused by the denial of rights frame which those subjects are immersed